Exponential Decay for Nonlinear von Kármán Equations with Memory. (10th December 2013) - Kang, Jum-Ran
Abstract : We consider the nonlinear von Kármán equations with memory term. We show the exponential decay result of solutions. Our result is established without imposing the usual relation between g and its derivative. This result improves on earlier ones concerning the exponential decay.